Five new secondary metabolites from an endophytic fungus Phomopsis sp. SZSJ-7B - Chen, Yan; Wang, Huan; Ke, Xin; Sang, Zihuan; Kuang, Min; Peng, Weiwei; Tan, Jianbing; Zheng, Yuting; Zou, Zhenxing; Tan, Haibo (Frontiers in Plant Science, 2022)
Two undescribed lactones phomolides A-B (1 and 2) and three new sesquiterpenoids phomenes A-C (3-5), together with one known compound colletotricholide A (6) were isolated from the endophytic fungus Phomopsis sp. SZSJ-7B. Their chemical structures including the absolute configurations were comprehensively established by extensive analyses of NMR, HRESIMS, ECD powered by theoretical calculations, and X-ray diﬀractions. Moreover, the cytotoxic and antibacterial activities of compounds 1-6 were also evaluated, and the results demonstrated that compound 2 showed significant antibacterial effects towards methicillin-resistant Staphylococcus aureus (MRSA) and S. aureus strains with MIC low to 6.25 μg/mL, which was comparable to that of the clinical drug vancomycin. Moreover, all compounds had no cytotoxic activity.